The Influence of Childhood Memories on Human Needs in Ishiguro’s "When We Were Orphans" - Ramadhani Dinda Lestari (Journal of Translation, Linguistics and Literature, 2024)
"When We Were Orphans," a book by Kazuo Ishiguro, examines the complex relationship that develops between early memories and human needs. Through the use of a psychoanalytic framework, the research reveals how Banks' early life experience impacted his adult desires and worldview. Shanghai both before and during the war serves as the backdrop for the story, offering a rich context for analyzing the characters' reactions to loss and displacement. This study investigates how Banks's longings for identity, connection, and a sense of belonging are shaped by nostalgia. This article advances our knowledge of the complex interplay between memories, trauma, and the search for identity in Ishiguro's "When We Were Orphans" by highlighting the story's investigation of these topics.